Enhancing Medication Safety in Saudi Healthcare: Implementation of Reconciliation at Admission and Discharge - Shorowk Alrumaihi,; Nour Homoud abdullah alanazi,; Abdulazizi Moburk Alasheer,; Abdullah Homud Almutairi,; Hashem Musaad Alzahrani,; Bander Mana Arishi,; Turki dhawi alotaibi,; Ibrahim Saleh Alfawzan,; Saeed mubarak almadhi,; Thamer Mohammed Albaqami, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Medication errors during transitions of care remain a significant threat to patient safety globally. In Saudi Arabia, studies reveal high rates of medication discrepancies during hospital admissions and discharges, underscoring the urgent need for systematic interventions. This paper examines the role of medication reconciliation (MedRec) as a strategy to reduce errors and enhance patient outcomes in Saudi healthcare settings. Drawing on evidence from multicentre studies, systematic reviews, and international frameworks, the paper outlines challenges, strategies, and policy recommendations for implementing MedRec. Key findings highlight the effectiveness of pharmacist-led interventions, multidisciplinary collaboration, and patient engagement. The integration of technology and adherence to accreditation standards, such as those by the Joint Commission International, are emphasized as critical success factors.